Bovine ischaemic teat necrosis: a further potential role for digital dermatitis treponemes. (16th January 2016) - Clegg, S. R.; Carter, S. D.; Stewart, J. P.; Amin, D. M.; Blowey, R. W.; Evans, N. J.
Abstract : A recent outbreak of ischaemic teat necrosis (ITN) on mainland UK has resulted in large economic losses for dairy farmers. Typical cases start as an area of dry, thickened and encrusted skin on the medial aspect of the base of the teat, where the teat joins the udder, often with a fetid odour. The erosion spreads down the teat, often causing intense irritation, which in turn leads to more severely affected animals removing the entire teat. Due to the severity of ITN and the substantial economic costs to the industry, analyses were undertaken to ascertain if an infectious agent might be involved in the pathology. The study has considered a role for digital dermatitis (DD) treponemes in the aetiopathogenesis of ITN because, as well as being the prime bacteria associated with infectious lameness, they have been associated with a number of emerging skin diseases of cattle, including udder lesions. A high association between presence of DD‐associated treponemes and incidence of ITN (19/22), compared with absence in the control population is reported. Furthermore, sequencing of the 16S rRNA gene of treponeme isolates supports the hypothesis that the identified treponemes are similar or identical to those isolated from classical foot DD lesions in cattle (and sheep). Further studies are required to allow effective targeted prevention measures and/or treatments to be developed.